Analysis of directions of digital technologies introduction into industrial complex - Balashova, Elena S; Maiorova, Kseniia S (Naučno-tehničeskie vedomosti SPbGPU. Èkonomičeskie nauki (Online), 2020)
In the last decade, advanced digital technologies have been actively introduced into the industrial complex leading to increased efficiency of enterprises through changes in their internal business processes, as well as modernization of all production facilities. Further active adoption of digital technologies and their practical application in national industrial companies will open even greater opportunities and economic benefits. As a result, the use of digital technologies in complex solutions will change the business environment, as well as increase competition for all industry enterprises. According to most experts, the scale of this transformation requires a systemic targeted vision of digitalization at the industry level. In the new conditions of development and digital transformation of the industrial complex, enterprises must face new challenges, develop internal business processes, focusing on new factors affecting the functioning and improvement of production. At this stage, this is possible thanks to the use of digital technologies, as well as the active development of new products of the industrial sector of the economy, which have completely new functions. This process will be possible in case of involvement of all participants of industrial transformation and digitization of all production processes. The transition to the digital platform of the industrial complex implies the transition of vertical and horizontal relationships between producer companies and customers, contractors, transport companies to digital format. Thus, a single digital industrial space will create a monitoring tool for the industrial complex of the Russian Federation, which will allow to react and make management decisions quickly. A digital space of this type will help national enterprises to become faster, more flexible and more competitive in both domestic and international markets. This study describes the modern technological way of digital economy. The authors analyzed digital transformation of domestic industrial enterprises in modern conditions and identified the main directions of introduction of digital technologies into the industrial complex.